2021
DOI: 10.26717/bjstr.2021.40.006397
|View full text |Cite
|
Sign up to set email alerts
|

"Tracheal Stenosis as a Consequence of Orotracheal Intubations and Mechanical Ventilation in Time of Pandemic"

Abstract: Tracheal stenosis, consisting of the narrowing of the caliber and the tracheal lumen due to the formation of fibrous tissue, caused by damage to the mucosa and cartilage, is one of the most frequent complications and the reason for admission to the emergency department in Post-intubated patients during the course of the disease produced by covid 19, due to the suffocation conditions presented by them. In this way, the direct association between tracheal stenosis and orotracheal intubation and mechanical ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Prior studies have demonstrated an increased risk of tracheal stenosis with prolonged mechanical ventilation [12][13][14]. This is primarily demonstrated in the setting of ventilation in orotracheal intubation, which often presents as the indication for performing a tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated an increased risk of tracheal stenosis with prolonged mechanical ventilation [12][13][14]. This is primarily demonstrated in the setting of ventilation in orotracheal intubation, which often presents as the indication for performing a tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may have symptoms such as trouble breathing, difficulty weaning from ventilation or decannulation, the need for additional procedures to address the stenosis, and an increased mortality risk [8,[10][11]. Tracheal stenosis has been frequently found to be associated with prolonged mechanical ventilation [12][13][14]. Other reported factors associated with tracheal stenosis include increasing age, female sex, smoking, and comorbidities including diabetes, gastroesophageal reflux disease (GERD), chronic obstructive pulmonary disease (COPD), hypertension, and obesity [8,13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%